2015
DOI: 10.1016/j.ijsu.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

An observational study investigating the effect of platelet function on outcome after colorectal surgery

Abstract: Although complication rates were higher in aspirin group, impaired platelet function within ranges seen with aspirin continuation did not affect complication severity or rate or blood transfusion use. Consequently, aspirin continuation may not affect clinical outcome in patients undergoing major colorectal surgery and requires further investigation with a large randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The aspirin test showed that P-selectin expression rose with the length of time between stopping aspirin and surgery. Although the proportion of patients with a complication, including those with hemorrhage, was higher in the aspirin group, P-selectin expression was not associated with complications or bleeding (43).…”
Section: Surgerymentioning
confidence: 73%
See 1 more Smart Citation
“…The aspirin test showed that P-selectin expression rose with the length of time between stopping aspirin and surgery. Although the proportion of patients with a complication, including those with hemorrhage, was higher in the aspirin group, P-selectin expression was not associated with complications or bleeding (43).…”
Section: Surgerymentioning
confidence: 73%
“…The question then arises as to whether this should be stopped temporarily before major surgery to prevent the perceived risk of increased operative blood loss. In an observational study, the effect of stopping aspirin preoperatively in 20 patients having colorectal surgery was assessed and compared with a group who were not on aspirin (43). P-selectin expression was lower on aspirin (Table I) and within 5 days of stopping aspirin prior to surgery.…”
Section: Surgerymentioning
confidence: 99%
“…The study demonstrated the effects of antiplatelet therapy being taken on admission with acute stroke on the measurements performed as part of the TARDIS study [Bath PM et al Remote assessment of platelet function in patients with acute stroke or transient ischaemic attack, Submitted (2016)]. The approach has also been used to assess the residual effects of aspirin in surgical patients from whom this antiplatelet agent had been withdrawn [56]. The approach is also finding a use for determining the efficacy of antiplatelet agents in veterinary medicine [57].…”
Section: Methods Based On Measurements Of Platelet Activation Markersmentioning
confidence: 99%